Bosnia and Herzegovina : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Bosnia and Herzegovina. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that the economy of Bosnia and Herzegovina is enjoying its fourth consecutive year of stable growth underpinned by the currency board. Export growth of 29 percent on the back of productivity gains, export price increases, and improvements in reporting following the introduction of the VAT, combined with robust domestic demand, pushed real GDP up 6 percent in 2006. Fiscal policy has thus far been prudent. This good overall picture reflects a benign external environment and the effects of past economic reforms.